Developing a Sustainability Evaluation Model for Mosque Digital Da'wah: Index Guidelines and Best Practices in Ponorogo - Asis Riat Winanto; Syarifan Nurjan; Syamsul Arifin; Jawwad Sulthon Habiby; Fifi Arisanti; Maryono Maryono; Corrienna Abdul Talib (Universitas Muhammadiyah Sidenreng Rappang, 2026)
This community service research aims to develop a sustainability evaluation model for mosque digital preaching programs through index guidelines and best practices in Ponorogo Regency. The implementation method was carried out through the stages of socialization, digital media management training, and assistance in formulating sustainability indexes for mosque managers. The data analysis technique used was descriptive qualitative and quantitative analysis to measure the level of readiness and effectiveness of technology adoption by the partners. The results of the activity indicate that the implementation of this evaluation model successfully significantly increased the digital literacy capacity of mosque managers and produced a standardized index guide capable of measuring program sustainability independently. In conclusion, the resulting sustainability evaluation model and index guidelines are proven to be effective and applicable in maintaining the consistency, quality, and long-term impact of digital preaching programs run by mosque communities in Ponorogo.